Moving the Equity Agenda Forward
XI, 378 p. 9 illus.
Keywords: This volume takes on the vital tasks of celebrating, challenging, and attempting to move forward our understanding of equity and diversity in science education. Organized thematically, the book explores five key areas of science education equity research: science education policy; globalization; context and culture; discourse, language and identity; and leadership and social networking. Chapter authors -- emerging to established US science education scholars -- present their latest research on how to make science interesting and accessible to all students. The volume includes international voices as well: Scholars from around the world crafted responses to each section. Together, authors and respondents attempt to refine our methods for examining equity issues across classrooms, schools, and policies, and deepen our understanding of ways to promote equity and acknowledge diversity in science classrooms. Moving the Equity Agenda Forward is endorsed by NARST: A Worldwide Organization for Improving Science Teaching and Learning Through Research. The volume gains authority from the fact that it was edited by one current and four former chairs of NARST’s Equity and Ethics Committee.